Next-Generation Solar Cells: Advancements in Materials, Architectures, and System Integration for A Sustainable Energy Future. (American Journal of Innovation in Science and Engineering, 2025)
The progress of durable solar renewable energy depends on developments in solar cell technology. Current market trends are predominantly focused on crystalline silicon-based solar cells; nevertheless, the pursuit of enhanced efficiency and cost reduction generates considerable interest in investigating other materials and device architectures. This paper provides a review of the next generation of solar cells; perovskite materials, organic polymers, and quantum dots are evaluated regarding their potential as low-cost efficiency photovoltaic systems. I cross into more recent device architectures, including tandems and multi-junctions, as well as cost reduction strategies across the solar cell value chain. Here, I also explore the issues and opportunities presented by these new technologies, underscoring that progress in materials science, device design, and system integration will be crucial to realizing a global clean energy future. In this overview, the future of solar cell research and development is addressed coherently, opening possibilities for widespread adaptation of solar energy and shifting towards a sustainable energy landscape.